Integrating Cultural Values Into Buddhist Sunday School Learning System - Andanti, Maria Fransisca; Sutikyanto, Sutikyanto (JURNAL INOVASI DAN MANAJEMEN PENDIDIKAN, 2024)
This paper draws upon the possibility of integrating cultural values into Indonesia's Buddhist Sunday School (BSS) learning system. It employed George’s (2008) library research methods consisting of motivation or assignment, imagination, research questions (brainstorming), research plan (strategy), reference works and databases (tools and tactics), sources, evaluation, insight, thesis, argument and outline, and drafting and revising. By reviewing 25 journal articles and books regarding with culture and education, this paper proposed three things to establish cultural-based religious learning in BSS, which are strengthening cultural content and values in the learning process, building a community-based learning, and involving parents.